2007
DOI: 10.1073/pnas.0708365104
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic changes in metabolic state during the life of a yeast cell

Abstract: Budding yeast undergo robust oscillations in oxygen consumption during continuous growth in a nutrient-limited environment. Using liquid chromatography-mass spectrometry and comprehensive 2D gas chromatography-mass spectrometry-based metabolite profiling methods, we have determined that the intracellular concentrations of many metabolites change periodically as a function of these metabolic cycles. These results reveal the logic of cellular metabolism during different phases of the life of a yeast cell. They m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
282
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(297 citation statements)
references
References 38 publications
13
282
0
2
Order By: Relevance
“…Several studies have shown the bulk of Rtt109 expression and activity is generally limited to yeast G1/S-phase (14,17,31,50). Interestingly, acetyl-CoA levels are low during cell cycle replication (51,52). Together, these observations suggest Rtt109 activation is regulated by the cellular acetyl-CoA concentration.…”
mentioning
confidence: 67%
“…Several studies have shown the bulk of Rtt109 expression and activity is generally limited to yeast G1/S-phase (14,17,31,50). Interestingly, acetyl-CoA levels are low during cell cycle replication (51,52). Together, these observations suggest Rtt109 activation is regulated by the cellular acetyl-CoA concentration.…”
mentioning
confidence: 67%
“…3B and Dataset S1). Another striking function conserved between the two systems includes the pentosephosphate pathway (23). This pathway plays a major role in the production of NADPH (a reduced form of NADP+), a key metabolite that provides the cell with reductive power, and which is involved in the production of intermediates for many biosynthetic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the YMC, a highly synchronized cell population undergoes robust oscillations in oxygen consumption and metabolism that are coupled to the cell cycle, during continuous glucose-limited growth (37,38). Microarray analysis of gene expression during the YMC has revealed that over half of all yeast genes are periodically expressed according to a specified logic.…”
mentioning
confidence: 99%